Health services utilization prior to amyotrophic lateral sclerosis diagnosis: A province‐wide study of individuals treated with riluzole in Ontario, Canada. Issue 6 (28th September 2021) - Campitelli, Michael A.; Abrahao, Agessandro; Maclagan, Laura C.; Fu, Longdi; Maxwell, Colleen J.; Swartz, Richard H.; Zinman, Lorne; Bronskill, Susan E.
Abstract: Introduction/Aims: Amyotrophic lateral sclerosis (ALS) symptoms mimic those of other conditions and often require multiple physician and healthcare contacts for investigation and accurate diagnosis. We examined the type and frequency of healthcare service utilization prior to ALS diagnosis and tracheostomy‐free survival by sex and rurality among individuals treated with riluzole in Ontario, Canada. Methods: This population‐based cohort study used administrative databases to identify patients aged 18+ y diagnosed with ALS and started on riluzole between April 2002–March 2018. Using Poisson regression, rate ratios of healthcare utilization and atypical diagnostic tests and unnecessary therapeutic interventions 5 y prior to ALS diagnosis were compared by sex and rurality. Tracheostomy‐free survival after diagnosis was compared between groups using Kaplan–Meier estimators and proportional hazards models. Results: A total of 1071 patients with ALS were identified with a mean age of 70 y; 563 (52.6%) were men and 134 (12.5%) were rural residents. The number of physician visits increased in the 18 mo prior to ALS diagnosis. We observed modest sex differences in healthcare utilization. Rural patients had lower neurologist visit rates (rate ratio [RR], 0.78; 95% confidence interval [CI], 0.70–0.87) and were significantly more likely to receive an atypical diagnostic test or unnecessary therapeutic intervention (RR, 1.80; 95% CI, 1.04–3.10). Tracheostomy‐free survival did not differ by sex (log‐rank P ‐value = .78) or rurality (log‐rank P ‐value = .84). Discussion: Given disparities observed in healthcare of rural ALS patients, policy strategies are needed to ensure all patients have timely access to care along the pathway from symptom onset to ALS diagnosis, to enable access to new therapeutics and clinical trials.